Pengaruh Strategi Know-Want to Know-Learned (KWL) terhadap Keterampilan Membaca Pemahaman di Kelas IV Sekolah Dasar - wanda, rianti; Sukma, Elfia; lubis, mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research is to know the influence of Know-Want to Know-Learned (KWL) strategy on student learning in understanding reading. This research is a quasi-experimental research. The research design used is nonequivalent control group design.The population is all students in class IV sdn 03 Simpang Haru Padang city. The sampling technique used is totality sampling. Based on the results of hypothesis test analysis at 5% significance level obtained t count> ttable (1.96152> 1.67412). The conclusion of this research is the influence of cooperative script model to student intensive reading in Indonesian Languange.